Modern markers of myth definition - Zhussupova, B.Zh. (NLC «Karaganda National Research University named after acad. Ye.A. Buketov», 2025)
The article attempts to philosophically consider the mythological worldview, on the one hand, as an early historical type of explanation and understanding of the world, and on the other, as a specific way of thinking and human attitude to the world, mixed with the play of feelings, original imagination. The prerequisites and features of the mythological worldview are revealed, the key markers of the mythological narrative that ensure the authenticity of the myth are highlighted, and the main functions of the myth are revealed. The concept of myth as a vivid expression of the autochthonous symbolic culture, which has not been fully unraveled in the modern world, is considered. This is precisely what caused the emergence of the main philosophical and cultural concepts of the interpretation of myth, contradictory and self-valuable, as well as the formation in this regard of various philosophical and cultural schools in understanding and comprehension of the myth. According to most researchers, it was the mythological picture that laid the foundation for all others, representing the “childhood” in the spiritual history of mankind. As is known, the foundations of spiritual and cognitive (cognitive) guidelines are laid in childhood, which means that the mythological worldview implicitly (indirectly), in a folded, embryonic state, contains markers of all subsequent worldview pictures — religious, philosophical, scientific. However, the ability to create myths has not “sunk into oblivion”. Moreover, modern myth-making is gaining visible momentum in various areas of human and social activity, destroying the usual markers of defining the mythological type of worldview.
Social philosophy - Әлеуметтік философия - Социальная философия
Keywords: myth; worldview; way of thinking; imagination; cultural schools; mythological markers; symbol; sacred; aesthetics; man; creativity